Pengaruh Gaya Kepemimpinan Terhadap Kepuasan Kerja Karyawan Pada PT. Lion Mentari Airlines - Yesa Martha Vita Simanungkalit; Endang Setyaningsih (Jurnal Ekonomi Sakti, 2018)
Leadership (leadership) can be said as a way of a leader (leader), in directing, encouraging, and regulating all the elements in an organization to realize a goal to be achieved, resulting in maximum employee performance. To achieve these goals must be sought on how a leader can provide encouragement to work morale to employees, so that the goals and objectives planned together can achieve the target. In addition, leaders can provide promotion for employees who have high achievements, creating job satisfaction for employees. By providing compensation, employees will have high job satisfaction and work morale to achieve a target. Job satisfaction is the emotional state of the employee where there is no meeting point between the value of the employee's work return from the company / organization and the level of remuneration that is desired by the employee. The research was conducted at PT. Lion Mentari Airlines. In conducting research the author uses multiple regression analysis methods and uses the coefficient of determination F test and T test to test hypotheses. Data collected through questionnaires distributed to 50 respondents of employees of PT. Lion Mentari Airlines. Of the three independent variables tested individually, the most dominant type of leadership in influencing employee satisfaction is the authoritarian leader type (X2).